O separacji między prawem i moralnością. Glosa do Czystej teorii prawa Hansa Kelsena - Huk, Marta (ETHICS IN PROGRESS, 2013)
This paper is dedicated to the problem of separation legal and moral order from the perspective of Kelsen`s Pure Theory of Law. In discussing the need for such a separation, the author shows its relevant consequences. According to the most controversial of them, the “amoral law” seems to be a very sovereign normative concept. But still another question arises – wouldlegal subjects be able to cooperate with the law when its effectiveness is only based on the coercive power and sanctions?